Novel utilization of coffee processing by-products: kombucha cascara originated from 'Gayo-Arabica'. Issue 1 (January 2021) - Muzaifa, M; Andini, R; Sulaiman, M I; Abubakar, Y; Rahmi, F; Nurzainura,
Abstract: One of the current significant environmental challenges that have to be dealt with the majority of farmer in Indonesia, especially those on Gayo highlands - is the absence of an optimal utilization of coffee by-products or waste, which is deliberately produced in a great amount during the coffee processing. The Gayo highlands are located in the middle regions of Aceh province and widely known as the most extensive arabica coffee plantation all over Indonesia, with a total area 101, 473 hectares. The aim of this research was to optimally utilize the by-products or the exfoliated cherry-pulp into the so called kombucha cascara bearing great economical potential. However, further information in terms of its optimum processing condition (the length of fermentation duration, concentration of kombucha starter) from the cherry pulp into kombucha cascara has been much unexplored. In order to reveal that, we were trying to apply the effects of wo determinants, namely: i) fermentation duration (8, 12 days); ii) starter concentration applied (3%, 5%, and 7%) on kombucha cascara's chemical parameters [pH, total phenolic amount, antioxidant activity] and sensory in the form of hedonic test. Such test enabled us in describing consumers' preference based on its 'pronounced' the taste. Results showed that pH was ranged from 2.63 until 3.10, meanwhile, a relatively high antioxidant activity ranging from 25.78 and 51.69% noted with a total phenolic compound between 64.00 - 105.20 mg GAE (Galic Acid Equivalent)/ml were measured. This can be inferred that quality was shown to be deliberately affected both by the length of fermentation and starter's concentration, albeit the first one was to be more affecting. The longer the fermentation period, the lower the acidity value, and interestingly, significant decreases by total phenolic compound and antioxidant activity were also measured. It is also concluded that 12-days fermentation process added with 5% started received the highest score for sensory test.